A proposal by reducing the mining social conflicts using the improved multi-criteria assessment model - Poterico, Julio G.; Laurente, Filomón (Edelweiss Applied Science and Technology, 2025)
A methodological tool for multi-criteria impact assessment has been developed for application in the productive-extractive industry, such as mining activity, with the aim of reducing social conflict. This assessment methodology is called the IMCA Model (Improved Multicriteria Assessment). It is a holistic and innovative methodology that includes the quantification of impacts evaluated from a comprehensive approach. Additionally, the IMCA Model offers other advantages; it is a participatory, inclusive, and binding tool, which allows for better and more reliable results aligned with reality due to its traceability for assessing externalities. The IMCA Model methodology encompasses technical-operational, economic, social, cultural, educational, environmental, and governance factors, among others, depending on the project's nature. This methodology also comprises five main assessment phases: 1) Participatory phase, 2) Statistical phase, 3) Application phase of the mathematical algorithm - IMCA Model, 4) Results socialization phase, and 5) Monitoring and surveillance phase. By measuring externalities in the influence areas of a productive-extractive project using the IMCA Model, it becomes a predictive evaluation tool, enabling the design of a sustainable coexistence model with local populations and environments.